Satellite tracking large numbers of individuals to infer population level dispersal and core areas for the protection of an endangered species. Issue 7 (20th March 2013) - Schofield, Gail; Dimadi, Alexandra; Fossette, Sabrina; Katselidis, Kostas A.; Koutsoubas, Drosos; Lilley, Martin K. S.; Luckman, Adrian; Pantis, John D.; Karagouni, Amalia D.; Hays, Graeme C.; Keller, Reuben
Abstract Aim Tracking the dispersal patterns and habitat use of migratory species is necessary to delineate optimal areas for protection, with large sample sizes being more representative of the population. Here, we examine the dispersal patterns of a key Mediterranean loggerhead turtle (Caretta caretta) breeding population to identify priority foraging sites for protection. Location Zakynthos Island, Greece and the wider Mediterranean. Method We examined the dispersal patterns and foraging sites of 75 adult loggerheads (n = 38 males and 37 females) tracked from the breeding area of Zakynthos Island (Greece) from 2004 to 2011. We then combined our data with published sea turtle literature to identify key foraging sites for protection. Results While both males and females exhibited similar dispersal patterns, about 25% males remained < 100 km of Zakynthos, whereas all females (except one) migrated > 200 km. Integration of our data with the wider literature isolated 10 core sites in proximity to existing protected areas, which could potentially protect 64% of the Zakynthos population, while five sites support individuals from at least 10 other loggerhead breeding populations. Main conclusions Due to the widespread availability of neritic foraging grounds across the Mediterranean, sea turtles from Zakynthos exhibit disparate dispersal patterns. However, protecting only a few objectively defined important sites can encompass a large proportion of the foraging areas used and hence have considerable conservation benefit.